You Can't Fix What You Don't Look At: Acknowledging Race in Addressing Racial Discipline Disparities. (February 2017) - Carter, Prudence L.; Skiba, Russell; Arredondo, Mariella I.; Pollock, Mica
Racial/ethnic stereotypes are deep rooted in our history; among these, the dangerous Black male stereotype is especially relevant to issues of differential school discipline today. Although integration in the wake of Brown v. Board of Education was intended to counteract stereotype and bias, resegregation has allowed little true integration. Thus, old patterns continue to be reinforced through the ongoing processes of implicit bias, micro-aggression, and colorblindness. Thus, to effectively address inequity, the role of race must be explicitly acknowledged in addressing racial disparities in discipline. We close with a set of recommendations for talking about and acting on racial disparities.